Suicídio em Botucatu: um estudo descritivo dos casos ocorridos em 2009 - López, Bárbara Estefania [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objective: To identify sociodemographic and psychological characteristics associated to cases of suicide recorded in Botucatu during 2009, from a secondary analysis of data obtained through semi-structured interviews with relatives or significant others in order to obtain a psychological autopsy of each case. Methodology: A descriptive study of all cases of suicide recorded in Botucatu County, Brazil, during 2009. Interviews took place between 2 and 11 months after the suicide, coordinated by the County Department of Health Mental Health, and conducted by mental health professional specially trained to this end. Results: Sociodemographic characteristics of the 21 cases of suicide recorded in 2009 as well as factors associated to the 14 cases in which it was possible to perform a psychological autopsy did not differ from data found in the national and international literature. Indication of depression, of mental health treatment and alcohol use were among the abovementioned factors. Most cases had given previous indications of their intention or wish to die in the year before their deaths, with a high demand for health care services in the month previous to the suicide. Conclusion: Suicide prevention strategies that have demonstrated effectiveness elsewhere could also do so in Botucatu

Objetivo: Identificar características sociodemográficas e psicológicas associadas aos casos de suicídio registrados em Botucatu no ano de 2009, a partir da análise secundária de dados obtidos por entrevistas semiestruturadas com familiares ou pessoas próximas aos falecidos para constituição da autópsia psicológica dos casos. Metodologia: Estudo descritivo de todos os casos de suicídio registrados no município de Botucatu, SP, em 2009. As entrevistas foram coordenadas pela Equipe de Saúde Mental da Secretaria de Saúde de Botucatu e realizadas entre 2 a 11 meses após os suicídios, por profissionais de saúde especialmente capacitados para esse tipo de entrevista. Resultados: Tanto as características sociodemográficas dos 21 casos, registrados em 2009, quanto os fatores relacionados aos 14 casos, nos quais foi possível realizar autópsias psicológicas, não discrepam dos dados encontrados na literatura nacional e internacional. Indícios de depressão, tratamento na área de saúde mental e uso de álcool estavam entre os fatores relacionados. A maioria dos casos demonstrou intenção ou desejo de morrer no ano anterior ao suicídio e houve uma elevada procura dos serviços de saúde no mês anterior ao suicídio. Conclusões: Estratégias de prevenção utilizadas em outros locais poderiam ter sua efetividade demonstrada no município de Botucatu
Suicide in Botucatu, Brazil: a descriptive study of cases that took place in 2009
Keywords: Suicídio; Pesquisa psicologica; Autópsia psicológia; Saúde pública; Psychological autopsy; Suicide; Botucatu (SP)